Oddziaływanie bezpośrednich instrumentów polityki rynku pracy na poziom bezrobocia w krajach OECD - Szymańska, Anita (The Influence of Direct Measures of Labour Market Policies on the Level of Unemployment in OECD Countries, 2009)
Unemployment benefits provide protection against labour market risk, while active labour market policies prevent this protection from prolonging unemployment duration by reducing search incentives of beneficiaries. Thus the two institutions are complementary. The appropriate design of labour market policies can provide very good results for the labour market performance, especially may reduce the level of unemployment and its persistence.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 393-403